Analisis Tradisi Wurumana Kematian Dalam Budaya Ende Lio Dan Dampaknya Pada Viability Ekonomi Masyarakat Desa Manulondo, Ndona Kabupaten Ende - Marianus Kejapilus Naga; Helena Rosalia Parera; Yulita Klaudia Sepe; Ermenlinda Saputri Weni; Angela Yolanda Mando (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
This research paper explores the tradition of “ Wurumana Kematian” in Manulondo village, Ndona sub-district, Ende district, Flores NTT. Wurumana is a customary tradition related to death, which also has a very deep cultural spiritual meaning and is passed down from generation to generation by the Ende Lio cultural community in general. This research discusses the wurumana tradition in Ende Lio vulture and its impact the economic viability of the community. Wurumana is a sharing tradition practiced by the Ende Lio community in important event such as marriage or wedding, circumcision, death and graduation. In this tradition. Various family parties are involved, including the ine ame, tuka bela aji ka’e and ana embu Wurumana also has a meaning of brotherhood that is prepared with the aim that, ehen another brother experiences grief due to death, then we as tuka bela and aji ka’e take part in the event. This study aims to understand how wurumana death is practiced, its role in the social life of the community and also the influence on the economic stability of the local community. Through a qualitative approach data was collected through in-depth interviews with traditional leaders (mosalaki: lio), as the main resource persons, participatory observation, and literature review. The result showed that the tradition of wurumana death is not only a ritual of respect for the deceased, but also a way to honor the dead.